Los prolegómenos del comunismo indo-afroamericano en Haití y Jacques Roumain: 1927-1933 - Vicente Romero (Les Cahiers ALHIM)
This article explores the beginnings of the Communism in Haiti. It keeps in mind the cosmopolitism and the Black-indigenous ideology of La Revue indigène (1927-1928) and within, the point of views expressed by the young poet Jacques Roumain. It takes account of the differentiation process developed in the Haitian nationalism between “Integral” and “Moderated” nationalism, and then, between Communist and Socialists in a hand, and “Negristes” in the other one. In the press of the Red International Trade-Union –Profintern and Communist International –CI, it follows some directions concerning Haiti between 1929 and 1933. It follows too the steps made by the militants of Communism even without party in Haiti. Then it essays to appraise the grade of singularity or synthesis attained by the Haitians from the Black-indigenous ideology and the Communism, it means, the degree reached to propose an Indo–Afro-American Communist politics ad-hoc for Haiti, underpinning since this years on the Ethnology and Linguistic sciences about the socio-cultural Creole and rural word of the Cultivateurs (ex-Bozals).